THE QUICK RESPOND INDONESIAN STANDARD (QRIS) PERFORMANCE: EVIDENCE FROM “Z GENERATION” GROUP - Muhammad Yoesoef, Yoesrizal (RADJA PUBLIKA, 2023)
This study aims to determine whether self-efficacy, personal attachment, privacy issues, and technological innovations influence the Quick Respond Indonesian Standard usage determination. The study approach is quantitative, using multiple linear regression statistical analysis. The research population of this study is the 100 Z generation in Lhokseumawe City. The data were collected from first-hand sources through a Likert-scale-based survey by sending questionnaires. The result analysis demonstrates that self-efficacy and privacy issues do not influence Gen Z determinants to use Quick Respond Indonesian Standard (QRIS). In contrast, personal attachment and technological innovations positively affect the Z generation to use the QRIS platform.